The Effect of Deferred Income Tax on the Profit of the Enterprise - Jonas, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article examines the discrepancy between accounting law and tax law regarding the determination of financial results (income) and the presentation of the role of deferred income tax in offsetting tax burdens so as to comply with superior accounting principles. The article analyses profit and loss accounts published by randomly selected entities from the list of the largest enterprises in Poland in 2016. It examines the relations that would appear if the entity determined and did not determine the deferred income tax as well as how the profit indicator in both situations would be shaped. Based on this analysis, a preliminary application on the essential impact of deferred income tax on the development of net profit was formulated. This conclusion, however, should be verified on a much larger research sample.